Average inflation targeting in Calvo model with imperfect knowledge and learning - Seppo Honkapohja; Nigel McClung (Bank of Finland, 2024)
Properties of average inflation targeting under imperfect knowledge and learning have been studied only for the Rotemberg NK model, where price stickiness arises from adjustment costs in price setting. This note fills the gap by studying average inflation targeting in the NK model with Calvo price stickiness. It is shown that in this setting the two models have the same basic properties, unless the central bank aggressively stabilizes output instead of average inflation.
urn:nbn:fi-fe2024111894883
Keywords: 330